4th Ditan International Conference on Infectious Diseases Beijing, China - Nabilah, Awang@ Ismail (Pusat Pengajian Sains Perubatan, 2010)
Transmission patterns of Trichomonas vagina/is among women population In Khartoum State M. Dahab1"', E. Osman2 , W. Koko1• 1 Medidnal and Aromatic Plants Research Institute, 2/nternational University of Africa, Khartoum, Sudan Objectives: A study was carried out from January 2008 to December 2008 to determine the transmission patterns of such Infection (prevalence and incidence) of trichomoniasis at two different localities In Khartoum State (urban and rural area). Methods: A standardized questionnaire and aU the subjects were followed by pelvic examination. Some of these samples were taken for follow up study (Incidence) and examinations of both samples by wet mount preparation. The study was consisted routine monthly prevalence carried to find out the risk factors related With trichomoniasis. Results: The present study found that 12.0% (297) out of 2473 were identified of "Sudanese women presenting to Ombadda and Ibrahim Malik hospitals were infected With trichomoniasis, no significant difference in the prevalence the distribution of urino·genital trichomoniasis in Ombadda and Ibrahim Malik Hospital (P > 0.05). In Alsalam administration unit gave the highest infection 75 (3.0%) With significant rate (P < 0.05), the highest Infection between age group 21l-24 years old was recorded among Sudanese women (P>0.05), the highest numbers of Infections were observed in October 49 (2.0%), Statistical analysis showed significant difference in the prevalence of infection monthly (P < 0.05), the highest infection 187 (7 .6%) was observed among the married and this result was significant With respect to marital status (P<0.05), T. vaginalis is higher common In non pregnant women than pregnant (P < 0.05), raise temperatures of water effect In viability of T. vaglnalis (P<0.05). The fumigation gave more effects in the parasite (P < 0.05). Incidence study for selected infected women (17 patients); the incidence rates turn down to zero infection after 2 months (5.8%); however after one month most the infected patient were treated for infection (11.8%). Conclusion: Increased prevalence of Trichomonas vagina/is Infection (12%) could also reflect lack of access to care and distrust of the health-care system; therefore, more efforts should be taken to control the problem. Other risk factors was determined such as the temperatures of water, fumigations and symptoms related With transmissions of Trichomonas vaginaUs, new effective strategies are needed to combat this infection. Acknowledgement: The authors are grateful to ministory of health, Sudan, Mr. Etyeb Fadul and laboratory practitioner Mrs. Aya Taha for their cooperation With this study.